ANALISIS KADAR GAS SULFUR DIOKSIDA (SO2) DI UDARA AMBIEN PADA INDUSTRI MAKANAN RINGAN YANG MENGGUNAKAN BRIKET BATUBARA DAN KELUHAN SALURAN PERNAFASAN PADA MASYARAKAT DI DESA BAKARAN BATU KECAMATAN BATANG KUIS KABUPATEN DELI SERDANG TAHUN 2013 - Rizka Fiqih Ertika; evi naria; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
Coal briquette been an solid fuel made from coal, solid fuel is alternative fuel or constituting a substitute kerosene the cheapest and predicted to developed in mass in a relatively short time considering technology and equipment used relatively simple. Sulfur dioxide gas is preeminently resulting from the burning fossil fuels such as coal. Research aims to know levels gas SO2 and complaint respiratory on society around food industry light that uses coal briquette in the Bakaran Batu village burnt stone sub-district Batang Kuis district Deli Serdang. The design of research is descriptive. Population in this research of 180 the housewife in hamlet 1 and 2. Samples totaled 58 people housewife with used technique the sample in simple random sampling. The object of the research was done. Data were analyzed by descriptive in the form of tables and narratives. The result showed that respondents from > 40 years ( 37.9 % ), the level of education highest is sma ( 56,9 % ), respondents have been living in the village of burnt offering stone > 20 years ( 53,4 % ). On the basis of the results obtained a picture that the level of air pollution by SO2 on the settlement near the snacks industry light that uses coal briquette in the village of burnt offering stone sub-district Batang Kuis value at the average of 52,27 µg/m3, Means levels of sulfur dioxide measured is still qualify in quality standards according to PP RI No.41 1999 that is, ( 900 µg/m3). The conclusion of this research is gas SO2 in the air ambient on snacks industry in the Bakaran Batu village of burnt offering stone does not exceed quality standards. The result analysis of data that respondents describe that experience complaints of the respiratory tract as many as 39,7%. Nevertheless other malignancies in a recurrent manner can cause respiratory disorders.   Keywords: Coal Briquette, The Concentration Of Sulphur Dioxide, Complaint The Respiratory Tract